Lead Removal from Agricultural Soil of Kurdistan Region by Fe3O4 Nanoparticles - Omar, Karzan A.; Omar, Nisar S. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2014)
Lead toxicity became a major concern worldwide and it is one of the most harmful pollutants in soil and groundwater. Hence, to remove lead from the soil, a high efficient technology with improved materials and system is required. This paper is a study shows removing of lead ions from soil samples, which have been taken from different sites in the Kurdistan Region, and investigated the adsorption of lead ions on high efficient adsorbent Fe3O4 nanoparticles. The magnetite nanoparticles of 27nm were synthesized by using a co-precipitation method and characterized by X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and scanning electron microscopy (SEM) equipped with energy dispersive X-ray spectroscopy (EDX). The adsorption experiments occurred at pH 8.0 under room temperature (25 °C) and the adsorption capacity was 22.8 mg/g which is 4 times higher than that of coarse particles. The correlation is measured between pH and absorbance, pH and concentration, electrical conductivity and concentration of lead ions in agricultural soil. These relationships indicate that the correlation coefficient values of (r = - 0.68, – 0.70 and + 0.83) are statistically significant at (ɑ= 0.05). The limit of detection (LOD) and limit of quantification (LOQ) were found to be 0.73 mg/L and 2.44 mg/L, respectively.